Regulations in Italy and health surveillance for manual load handling: New developments from the supreme court and risk prevention - Angelo SACCO (GIornale Italiano di Psicologia e Medicina del Lavoro)
Italian regulations for protecting workers involved in manual load handling are outlined in Legislative Decree 81/2008. This decree mandates that employers adopt organizational measures and mechanical equipment to prevent or mitigate biomechanical overload risks, especially for the lower back. When manual handling cannot be avoided, employers must provide suitable tools and measures, as indicated in Annex XXXIII. Health surveillance is mandatory for all involved workers to identify hypersusceptibility conditions, such as pregnancy or physiological issues, that could impair physical capability. Rulings by the Italian Supreme Court (2023, 2019) have upheld the obligation for health surveillance even when risks are deemed low. The surveillance protocol should not only focus on biomechanical overload but also consider the functional status of target organs and systems, such as the cardiovascular and respiratory systems, to ensure worker safety and health.